Sustainable Ecosystem: Forging A New Human— Plant Relationship - Mani Singh,; P. K. Singh, (SCHOOL SCIENCE, 2018)
It is impossible to imagine a life in isolation on this planet. Different forms of lives are associated with flora, fauna and atmosphere around them in the ecosystem. Being the producer, plants play a key role in the ecosystem. One of the most interesting features of life on this planet is its extraordinary diversity. We share planet Earth with countless other species who provide us essential goods for life including food, drugs, industrial products, genetic resources and much more. Earlier we were dependent on forests for all our needs. However, over time agriculture and industries emerged as new means to fulfil our desired needs. A harmonious balance among different biotic and abiotic components of an ecosystem is highly essential. However, over industrialisation and growth of the human population as well as the increased requirements of food and other essentials have stressed the natural system. It has given rise to the pollution of air, water and soil and degraded many habitats which has threatened the survival of many species. The plants check air pollution by reducing the amount of carbon dioxide in the air and supplying oxygen through photosynthesis. Plants help cleaning up of synthetic chemicals and bacteria from water and soil as well as help in minimising undesirable noise pollutions. They prevent soil erosion, filter dust and cool atmosphere in neighbour hoods. For wildlife, the plants can be their food source as well as their home. In fact plants play a crucial role in almost all the aspects of life. They support us as good friends through thick and thin. Majority of the environmental issues created due to unbalanced growth can also be solved with the help of technologies, treaties and trees